1998
DOI: 10.1002/(sici)1097-0134(19980301)30:4<442::aid-prot11>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and spectroscopic characterization of a molecular hinge: Conformational changes in bothropstoxin I, a dimeric Lys49-phospholipase A2 homologue

Abstract: Bothropstoxin I (BthTX-I) from the venom of Bothrops jararacussu is a myotoxic phospholipase A2 (PLA2) homologue which, although catalytically inactive due to an Asp49-->Lys substitution, disrupts the integrity of lipid membranes by a Ca2+-independent mechanism. The crystal structures of two dimeric forms of BthTX-I which diffract X-rays to resolutions of 3.1 and 2.1 angstroms have been determined. The monomers in both structures are related by an almost perfect twofold axis of rotation and the dimer interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
67
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 51 publications
8
67
0
4
Order By: Relevance
“…"SequenceSpace" analysis (42) and x-ray diffraction studies (32)(33)(34)(43)(44)(45)(46) have both clearly shown that, with the exception of Asp 49 itself, the Lys 49 -PLA 2 s conserve all the important residues of the catalytic machinery, as well the nucleophilic water molecule and a hydrogen-bonding network that involves Tyr 52 and Tyr 73 and the N terminus. In addition, crystallographic structures in complex with naturally bound fatty acid molecules (interpreted as the product of catalysis) have been described (46,47). Based on these results, Lee and co-workers (47) have suggested that the apparent low level or lack of catalytic activity for Lys 49 -PLA 2 observed in vitro could be the result of the failure of product release from the active site after one cycle of catalysis, leading to enzyme inhibition.…”
mentioning
confidence: 99%
“…"SequenceSpace" analysis (42) and x-ray diffraction studies (32)(33)(34)(43)(44)(45)(46) have both clearly shown that, with the exception of Asp 49 itself, the Lys 49 -PLA 2 s conserve all the important residues of the catalytic machinery, as well the nucleophilic water molecule and a hydrogen-bonding network that involves Tyr 52 and Tyr 73 and the N terminus. In addition, crystallographic structures in complex with naturally bound fatty acid molecules (interpreted as the product of catalysis) have been described (46,47). Based on these results, Lee and co-workers (47) have suggested that the apparent low level or lack of catalytic activity for Lys 49 -PLA 2 observed in vitro could be the result of the failure of product release from the active site after one cycle of catalysis, leading to enzyme inhibition.…”
mentioning
confidence: 99%
“…The crystal structure of native Bothropstoxin I (BthTX-I) has been solved (da Silva-Giotto PSFG 1998) [13], however, the coordinates are not available in the RCSB Protein Data Bank in order to perform structural comparative studies with different complexes.…”
Section: Introductionmentioning
confidence: 99%
“…A cinética de permeabilização da membrana externa de E.coli é rápida e dependente da concentração de "Sytox green", oxonol, rodamina, iodeto de propídio e TO-PRO-1 e a maioria dos estudos encontrados na literatura, que utilizam tais sondas, investiga a susceptibilidade e viabilidade bacteriana devido à ação de agentes antimicrobianos (ROTH et al, 1997;MORTIMER et al, 1999;GANT et al, 1993;LEBARON et al, 1998 e estudos de mutagênese sítio dirigida de resíduos na interface dimérica (RULLER, 1999), o envolvimento da extensão C-terminal no mecanismo danificador de membranas já havia sido proposto (DA SILVA GIOTTO et al, 1998). Estudos cristalográficos e espectroscópicos de BthTx-I mostraram que a interface dos monômeros forma uma "dobradiça" que resulta nas formas "aberta" e "fechada" do dímero.…”
Section: Bthtx-iunclassified
“…Na natureza, as PLA 2 s-Lys49 existem em solução em formas diméricas (FRANCIS et al, 1991;DA SILVA GIOTTO et al, 1998;DE OLIVEIRA et al, 2001). Estudos cristalográficos e espectroscópicos de BthTx-I, uma PLA 2 -Lys49 do veneno de Bothrops jararacussu, mostraram que a interface dos monômeros forma uma "dobradiça" que resulta nas formas "aberta" e "fechada" do dímero (figura 5).…”
Section: Introductionunclassified
See 1 more Smart Citation